MENERAPKAN APLIKASI GIS UNTUK MENGETAHUI LOKASI DAN KEBUTUHAN SEKOLAH (Studi Kasus di Dinas Pendidikan Mukomuko) - Radius Prawiro; Azrai Sirait (Universitas Asahan, 2018)
Abstract - The content of this study is the construction of a Geographic Information System. The development of this Geographic Information System is expected to help the Education Office to record school needs displayed in the form of maps. In addition, it helps the community to know the location and needs of the school. This Geographic Information System is displayed in a web form so that everyone can access it. In building this Geographic Information System, the author uses google maps to determine coordinates. This coordinate point is the latitude and longitude points found on google maps. Using these coordinates, you will get the school location. Latitude and longitude values will be stored in the MySQL database and will be called using PHP programming. This Geographic Information System can run locally, namely using a local server such as XAMPP, provided that it must be connected to the internet. Geographic Information System Design uses UML modeling consisting of usecase, activity diagrams, class diagrams, sequential diagrams, statechart diagrams, package diagrams, component diagrams, deployment diagrams, and collaboration diagrams. Keywords - Geographic Information Systems, Google Maps, Latitude, Longitude, UML